OP73 Physical capability in midlife and survival over 13 years of follow-up in a British birth cohort study. (2nd September 2014) - Cooper, R; Strand, BH; Hardy, R; Patel, KV; Kuh, D
Abstract : Background: Better performance in objective tests of physical capability, including stronger grip and faster walking speed, has consistently been linked to lower all cause-mortality rates in community-dwelling older populations. It remains unclear whether associations are also found in younger populations who have higher mean levels of physical capability and less disease burden. We aimed to: examine the associations of three objective measures of physical capability (grip strength, chair rise speed and standing balance time) assessed in midlife with all-cause mortality rates over 13 years of follow-up; and assess the added value of these measures. Methods: 1355 men and 1411 women from the MRC National Survey of Health and Development whose physical capability had been assessed at age 53 (in 1999) and who were linked to the NHS Central Register for mortality notification were included in analyses. Using Cox proportional hazards regression models we tested the associations of: (1) each of the three physical capability measures; (2) a composite physical capability score; and (3) the number of tests participants were unable to perform, with subsequent hazards of all-cause mortality. Follow-up was from March 1999 until confirmed death from any cause, emigration or the end of March 2012. Adjustments were made for gender, body size, socio-economic position, lifestyle factors and health status. Results: Those participants in the lowest performing sex-specific fifth of each physical capability test and those unable to perform the test were found to have higher mortality rates than those in the highest fifth. Adjustment for baseline covariates partially attenuated associations but in fully adjusted models the main associations remained; the fully-adjusted hazard ratio (HR) (95% CI) of all-cause mortality when comparing the lowest with the highest fifth of a composite score of physical capability was 3.68 (2.03–6.68). Those people who could not perform any of the tests had higher rates of death when compared with those people able to perform all three tests; fully-adjusted HR=8.40 (4.35–16.23). When a series of models including different combinations of the measures were compared using likelihood ratio tests, all three physical capability measures were found to improve model fit and a model including all three measures produced the highest estimate of predictive ability (c-index= 0.71 [0.65–0.77]). Conclusion: Our findings demonstrate value in the objective assessment of physical capability in midlife. Even at this relatively young age these measures identify groups of people who are less likely to achieve a long and healthy life.